The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1475-1313.2003.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the Stiles–Crawford effect of the first kind (SCE‐I) and myopia

Abstract: The Stiles-Crawford effect of the first kind (SCE-I) was measured on both emmetropic and myopic subjects at six different retinal locations. The results revealed a number of significant discrepancies in receptor alignment between the groups of different refractive errors. In myopic subjects, the receptors in the nasal retina (i.e. between the fovea and the optic nerve head) were found to be aligned nasally towards the optic nerve head, whereas the receptors in the temporal retina were aligned towards the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 6 publications
5
42
0
Order By: Relevance
“…Variables affecting the Stiles-Crawford effect include luminance [11][12][13], wavelength [11,14], and retinal eccentricity [15][16][17]. Choi et al [17] reported that emmetropes have greater directionality than myopes between 10 nasal and 15 temporal retina.…”
Section: Introductionmentioning
confidence: 99%
“…Variables affecting the Stiles-Crawford effect include luminance [11][12][13], wavelength [11,14], and retinal eccentricity [15][16][17]. Choi et al [17] reported that emmetropes have greater directionality than myopes between 10 nasal and 15 temporal retina.…”
Section: Introductionmentioning
confidence: 99%
“…So saying, it is known that PVD occurs quite a bit earlier in age in high myopes. We deduced from our study that eye movements and associated optic nerve 'tugs' were likely contributory sources of the measured traction effects [19]. There needs to be a more definitive study of this set of issues.…”
Section: Traction Effectsmentioning
confidence: 83%
“…[3,17,18]. In a separate study, this apparent effect was differentiated from strains induced by vitreous body adhesions to the retina and optic nerve head [19]. The latter study led directly to this research.…”
Section: Traction Effectsmentioning
confidence: 95%
See 2 more Smart Citations